2006
DOI: 10.1007/s00441-005-0117-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of human dental pulp cells: various isolation methods and culturing environments

Abstract: Our purpose was to characterize human dental pulp cells isolated by various methods and to examine the behavior of cells grown under various conditions for the purpose of pulp/dentin tissue engineering and regeneration. We compared the growth of human pulp cells isolated by either enzyme digestion or the outgrowth method. Expression of dentin sialophosphoprotein, Cbfa1, and two types of collagen (I and III) in these cells was examined by Western blot or reverse transcription/polymerase chain reaction. Growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
176
0
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(202 citation statements)
references
References 42 publications
14
176
0
12
Order By: Relevance
“…However, this process can cause cell damage and induce cell death if not done properly. 23 All evaluated articles in our study described the enzyme used for DPSCs dissociation. Only five families of enzymes were mentioned: collagenase, dispase, trypsin, thermolysin and DNAase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this process can cause cell damage and induce cell death if not done properly. 23 All evaluated articles in our study described the enzyme used for DPSCs dissociation. Only five families of enzymes were mentioned: collagenase, dispase, trypsin, thermolysin and DNAase.…”
Section: Discussionmentioning
confidence: 99%
“…18 Few studies have compared the enzymatic and explant techniques for DPSCs isolation. 23,29,31 In a well-designed study, Hilkens and collaborators showed that cells isolated by the enzymatic or the explant techniques had the same proliferating rate and colony formation capacity, and could successfully differentiate into adipogenic, chrondrogenic and osteogenic cell types, indicating that both isolation methodologies could be applied to obtain suitable autologous DPSCs. 29 One particular aspect of the explant technique is the size of tissue fragments.…”
Section: Discussionmentioning
confidence: 99%
“…New blood vessels also penetrated the cells/PGA implants in vivo 3 weeks after the implantation. Since the isolation and characterization of DPSCs and SHED (6,16), using these stem cells for dentin/pulp tissue regeneration has drawn great interest (47)(48)(49).…”
Section: Stem Cells For Pulp/dentin Tissue Engineering and Regenerationmentioning
confidence: 99%
“…Collagen has been considered as a convenient pulp cell carrier and could conveniently be injected into canal space to regenerate pulp clinically, yet collagen as the matrix has been found to contract significantly when carrying pulp cells (47,57), which may considerably affect pulp tissue regeneration. Our in vivo experiments using mouse as a study model showed that when pulp cells were cast into collagen gel and placed into a canal space, the contraction interfered in the pulp regeneration.…”
Section: Stem Cells For Pulp/dentin Tissue Engineering and Regenerationmentioning
confidence: 99%
“…The enzymatic digestion process involves the application of the enzymes collagenase I and dispase in direct contact with the tissue, in order to disaggregate the tissue and obtain cell suspension. In this way, the released stem cells can adhere quickly to the bottom of the culture dish with greater ease 14 . With the explant technique, the tissue does not undergo any method of cell dissociation, however, the tissue is fragmented into several pieces and deposited on culture dishes (Figure 2).…”
Section: Isolation Methods For Stem Cellsmentioning
confidence: 99%